Sekuritisasi Isu Separatisme Oleh India Sebagai Justifikasi Pencabutan Otonomi Kashmir - Syahputra Daulay, Harry Prananda; Apriwan; Virtuous Setyaka (Palito, 2023)
This study examines the securitisation of Kashmir's separatism by the Indian government. This study argues that the government of India's securitisation effort seems like an initial step to revoke Kashmir's special autonomy. This study employed a securitisation framework, emphasising how two main stages of securitisation shape and influence the securitising process, including raising the issue and convincing the audience. I used a qualitative method by using descriptive analysis and secondary data sources. The Finding highlights that in the staging of raising the issue, the Indian government used media and political parties as speech act arena. In convincing the audience, Indian political elites and Indian society become other domains in addressing Kashmir's separatism. Consequently, this thesis argues that revoking Kashmir's autonomy becomes a rational action and has acceptability in public discourse. Keywords: India, Narendra Modi, Securitization, Separatism.